The abortion as a health problem in metropolitan Piura - Valera, Daniel (2015)
We studied the incidence, distribution and rate of maternal death due to abortion in Piura, a city in the north coast of Peru. In health establishments, tip to 1996, 10,7 of gestations finished in abortion. Abortion rate was 122,5 per 1000 live new horn and 8,9% of the abortions were infected. Septic abortion was the third cause of maternal death in the last 4 years, representing 18,5%, behind eclampsia mid sepsis and before obstetric hemorrhage. Maternal death due to abortion in Piura in 1996 was 41 x 100 000 ab. (27,3% of total). The Regional Hospital concentrated all the cases of maternal death due to abortion. Rate was 150 x 100 000 ab (general rate of maternal death was 552 x 100 000 ab). The Regional Hospital presented high scores of abortion cases in comparison to the rest of health establishments because of patients reference.